Social Support and Psychological Well-being of Teachers in Public Secondary Schools In Edo State, Nigeria - Osunde, Yvonne Ododo (International Journal of Applied Guidance and Counseling, 2026)
This study examines how social support from family and colleagues relates to the psychological well-being of public school teachers in Edo State, Nigeria. Using a survey, 292 teachers from 10 secondary schools in Oredo Local Government Area participated, with data collected via questionnaires and analyzed through descriptive and inferential statistics. Results revealed a significant positive relationship between social support and teachers’ psychological well-being, with both family and colleague support identified as key predictors. The findings highlight the importance of fostering supportive social environments in schools to enhance teacher well-being. Recommendations include creating collaborative school cultures through team-building activities and regular staff meetings, implementing colleague support programs, promoting work-life balance through family-friendly policies, and offering training and resources on stress management, mindfulness, and self-care, along with access to counseling and wellness programs. These measures can guide policymakers, educators, and mental health professionals in improving teachers’ psychological health and overall job satisfaction.